2017
DOI: 10.1111/tpj.13487
|View full text |Cite
|
Sign up to set email alerts
|

MYB12 and MYB22 play essential roles in proanthocyanidin and flavonol synthesis in red‐fleshed apple (Malus sieversii f. niedzwetzkyana)

Abstract: Flavonoids are major polyphenol compounds in plant secondary metabolism. Wild red-fleshed apples (Malus sieversii f. niedzwetzkyana) are an excellent resource because of their much high flavonoid content than cultivated apples. In this work, R6R6, R6R1 and R1R1 genotypes were identified in an F segregating population of M. sieversii f. niedzwetzkyana. Significant differences in flavonoid composition and content were detected among the three genotypes by ultra-performance liquid chromatography/quadrupole time-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
228
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(237 citation statements)
references
References 76 publications
9
228
0
Order By: Relevance
“…However, MdTTG1 (WD40 class) neither interacts with MdMYB1 nor binds to the promoters of MdDFR and MdUFGT but may interact with MdbHLH3 and MdbHLH33 to regulate anthocyanin synthesis (An, Tian, Chen, Wang, & Hao, ). MdbHLH33 interacts with MdMYB16, which inhibits anthocyanin biosynthesis via the C ‐terminal EAR repressor, to weaken its inhibitory effect (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, MdTTG1 (WD40 class) neither interacts with MdMYB1 nor binds to the promoters of MdDFR and MdUFGT but may interact with MdbHLH3 and MdbHLH33 to regulate anthocyanin synthesis (An, Tian, Chen, Wang, & Hao, ). MdbHLH33 interacts with MdMYB16, which inhibits anthocyanin biosynthesis via the C ‐terminal EAR repressor, to weaken its inhibitory effect (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional regulation of flavonol synthesis was investigated in Arabidopsis initially (AtMYB12) (Mehrtens, Kranz, Bednarek, & Weisshaar, ; Stracke et al, ), with flavonol MYB regulating factors subsequently found in grape (VvMYBF1) (Czemmel et al, ). Recently, MdMYB22, the transcription factor involved in apple flavonol synthesis, has been identified as a homologue of AtMYB12 (Wang et al, ). This study shows that expression patterns of MYB22 correlate with FLS expression during apple fruit development and suggests that MYB22 activates the flavonol pathway by combining directly with the FLS promoter.…”
Section: Introductionmentioning
confidence: 99%
“…This study shows that expression patterns of MYB22 correlate with FLS expression during apple fruit development and suggests that MYB22 activates the flavonol pathway by combining directly with the FLS promoter. With key players in the genetic control of flavonol and anthocyanin synthesis found, the impact of light exposure on apple flavonoid biosynthesis has begun to receive more attention (Feng, Li, Ma, & Cheng, ; Peng et al, ; Vimolmangkang et al, ; Wang et al, ), yet there is a lack of understanding regarding the role of UV light as a key driver of flavonoid regulation in apple.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that UGT can affect the accumulation of anthocyanins whereas MYB12 plays an essential role in proanthocyanidin synthesis (Cheng et al, ; Wang, Xu, et al, ). Indeed, the levels of anthocyanins in the STTM1916 and Anti‐miR1916 transgenic plants were significantly higher than the level found in the control plants (Figure ).…”
Section: Discussionmentioning
confidence: 97%